2000
DOI: 10.1084/jem.191.6.977
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the Bcr-Abl Kinase Activity Induces Apoptosis of Chronic Myelogenous Leukemia Cells by Suppressing Signal Transducer and Activator of Transcription 5–Dependent Expression of Bcl-XL

Abstract: Bcr-Abl–expressing leukemic cells are highly resistant to apoptosis induced by chemotherapeutic drugs. Although a number of signaling molecules have been shown to be activated by the Bcr-Abl kinase, the antiapoptotic pathway triggered by this oncogene has not been elucidated. Here, we show that the interleukin 3-independent expression of the antiapoptotic protein, Bcl-xL, is induced by Bcr-Abl through activation of signal transducer and activator of transcription (Stat)5. Inhibition of the Bcr-Abl kinase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
285
4
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(318 citation statements)
references
References 36 publications
21
285
4
8
Order By: Relevance
“…Previous studies have suggested that altered apoptotic signaling in Abl-expressing cells is associated with increased expression of several antiapoptotic proteins, such as BCL2 and BCL-XL, and inactivation of proapoptotic protein BAD (Banerjee and Rothman, 1998;Horita et al, 2000;Chen et al, 2008). Therefore, we analyzed the protein levels or phosphorylation status of these apoptotic proteins in v-Abl transformants expressing AKT1(WT), AKT1(E17K) or GFP.…”
Section: Akt1 Mutation Promotes V-abl Transformation G Guo Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that altered apoptotic signaling in Abl-expressing cells is associated with increased expression of several antiapoptotic proteins, such as BCL2 and BCL-XL, and inactivation of proapoptotic protein BAD (Banerjee and Rothman, 1998;Horita et al, 2000;Chen et al, 2008). Therefore, we analyzed the protein levels or phosphorylation status of these apoptotic proteins in v-Abl transformants expressing AKT1(WT), AKT1(E17K) or GFP.…”
Section: Akt1 Mutation Promotes V-abl Transformation G Guo Et Almentioning
confidence: 99%
“…Previous experiments have shown that BCL2 protein levels decline after the loss of v-Abl kinase activity (Horita et al, 2000;Chen et al, 2008). In an attempt to gain a better understanding of the molecular basis of the altered apoptosis profile in AKT1(E17K)-expressing cells, we evaluated the protein levels or phosphorylation status of BCL2 and BAD in the v-Abl-transformed cells ectopically expressing AKT1(WT), AKT1(E17K) or GFP.…”
Section: Akt1(e17k) Delays Apoptosis Induced By Imatinib By Regulatinmentioning
confidence: 99%
“…In this study we have shown that lack of activation of the BCR/ABLdependent signaling pathway(s) due to the mutation/ deletion of the particular BCR/ABL domain could be rescued by the alternative mechanisms. Activation of Akt serine/threonine kinase and STAT5 transcription factor is essential for leukemogenesis induced by BCR/ ABL (Skorski et al, 1997a;DeGroot et al, 1999;Sillaber et al, 2000;Horita et al, 2000;Neshat et al, 2000). Stimulation of Akt may depend on the intact SH2 domain of BCR/ ABL (Skorski et al, 1997a), but Akt was found activated in 32DcI3 cells expressing BCR/ABL DSH2 mutant after several weeks of in vitro culture.…”
Section: Resultsmentioning
confidence: 99%
“…This phenotype is associated with enhanced expression/activation of several e ectors (Raitano et al, 1997;Sattler and Salgia, 1997) such as Ras (Skorski et al, 1994;Sawyers et al, 1995), Rac (Skorski et al, 1998b), Raf-1 (Skorski et al, 1995a), PI-3k (Varticovski et al, 1991;Skorski et al, 1995cSkorski et al, , 1997a, Akt (Skorski et al, 1997a;Neshat et al, 2000), Bcl-2 (Sanchez-Garcia and Grutz, 1995), nuclear factor (NF)-kB (Reuther et al, 1998), CRKL (Senechal et al, 1996;Bhat et al, 1997), and STAT5 (Carlesso et al, 1996;Frank and Varticovski, 1996;Ilaria and VanEtten, 1996;Shuai et al, 1996;Chai et al, 1997;Nieborowska-Skorska et al, 1999;DeGroot et al, 1999;Sillaber et al, 2000;Horita et al, 2000). These proteins are stimulated by various functional domains/motifs of BCR/ABL (Pendergast et al, 1993a, b;Afar et al, 1994;Goga et al, 1995;Cortez et al, 1995;Anderson et al, 1996;Skorski et al, 1997a;Salomoni et al, 1998;Nieborowska-Skorska et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Bcl-X L transcription is an event that follows the constitutive activation of the STAT5 antiapoptotic pathway in BCR/ABL-transformed cells. [136][137][138][139][140][141] Since the nuclear export of Bcl-X L mRNA most likely depends on the nucleocytoplasmic shuttling activity of hnRNP A1, it is possible that, in BCR/ ABL-expressing cells, expression of antiapoptotic factors like Bcl-X L is not only controlled at a transcriptional but also at post-transcriptional level, through the activity of specific RNAbinding proteins. Interestingly, because hnRNP A1 was also recently described as a regulator of cap-independent IRESmediated mRNA translation, 142 it is conceivable that the translation regulatory function of hnRNP A1 might contribute to the leukemic phenotype of BCR/ABL-expressing cells.…”
Section: Bcr/abl Rna Binding Proteins and Translational Regulation Omentioning
confidence: 99%